Was the Pearl Poet in Aquitaine with Chaucer? A Note on Fade, 1.149 of Sir Gawain and the Green Knight - Revard, Carter (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen